Public knowledge and attitude toward basic life support in Jeddah, Saudi Arabia - Abbas, Haytham Abdulnasser; Khudari, Safa Yousef; Almalki, Rawan Hamed; Abed, Raghad Taher; Sait, Salam Atif; Sulaiman, Afnan Ahmad (International Journal Of Community Medicine And Public Health, 2021)
Background: Basic life support (BLS) is an integral component of initial resuscitative care during critical situations like sudden cardiac arrest, stroke, and airway obstruction. Tragic consequences of such life-threatening emergencies can be prevented with adequate knowledge and training on BLS principles. This study sought to assess the current status of public knowledge and attitude towards BLS in Jeddah, Saudi Arabia. Methods: Using a descriptive cross-sectional design, a study was conducted amongst residents of Jeddah, during July 2020. Participants were asked to fill a validated online questionnaire consisting of 9 demographic items, and 23 items determining attitude and general knowledge on BLS and cardiopulmonary resuscitation (CPR). Results: A total of 740 participants completed the questionnaire, with the majority being between 18 to 39 years old. Overall, the study findings show inadequate levels of BLS knowledge, with a mean knowledge score of 5.3 (SD±2.8) out of 15. The highest rates of correct responses were observed in the question concerning the recognition of the national emergency contact number (72.3%). Participants who had previously received BLS training had significantly higher knowledge scores (p<0.001), as well as those who took BLS courses within one year or less (p<0.001), and those who previously witnessed CPR (p<0.001). Conclusions: In general, knowledge about BLS among the participants was very limited, yet a positive attitude towards BLS training was observed. Therefore, a nation-wide effort is advised to enhance the public exposure on BLS.